The Community Service as Judges in an Elementary Level English Vocabularies Competition at SDN 137/III Koto Salak - Zaswita, Hermi; Amri, Zul (Jurnal Pengabdian Masyarakat Bangsa, 2023)
This community service activity is participation as judges in an elementary school English vocabulary competition at SDN 137/III Koto Salak. It aims to improve students' English vocabulary skills, learning motivation, and development of communication skills. The students learn about good preparation and teamwork through healthy competition. It also involves the community as volunteers and spectators, strengthening the relationship between the school and the surrounding environment. The results of this activity include increasing vocabulary skills, learning motivation, developing communication skills, and achievement awards. In this community service, good cooperation is needed between the school, judges, and community as well as evaluation and improvement for similar activities in the future. Utilizing these suggestions, this event is expected to be developed continually and provide greater benefits to participants, teachers, and the community in strengthening English language education.